Implementing Total Quality Management (TQM) in Education: Enhancing Competitive Advantage and Sustainable Performance in Educational Institutions - Asep Rosidin; Endang Herawan; Diding Nurdin (AL-ISHLAH: Jurnal Pendidikan, 2025)
In an increasingly competitive educational landscape, Total Quality Management (TQM) offers a strategic approach to enhance institutional quality, stakeholder satisfaction, and long-term sustainability. Despite its potential, consistent implementation of TQM remains challenging due to limited resources, institutional readiness, and cultural variations. This study investigates how TQM can be effectively adapted in Indonesian secondary schools by incorporating culturally relevant leadership practices—an area that remains underexplored. A qualitative case study approach was employed, involving three public high schools in Bandung Regency, Indonesia. Data were collected through in-depth interviews, direct observations, and document analysis to understand TQM implementation in these educational settings comprehensively. The findings indicate that TQM practices have contributed to improvements in school accreditation scores, stakeholder engagement, and operational efficiency. Notably, culturally embedded leadership approaches enhanced stakeholder trust and alignment with local values. However, challenges persist in the form of limited training opportunities, resource constraints, and inconsistencies in cultural adaptation, which have impeded the full realization of TQM benefits. This study demonstrates that while TQM can substantially improve educational quality and institutional competitiveness, its long-term success depends on sustained investment in capacity-building, culturally responsive leadership, and strategic resource allocation. The integration of local leadership values within TQM frameworks emerges as a critical factor for effective adaptation in Indonesian schools. These insights are transferable to other contexts facing similar barriers in implementing quality management systems in education.